SolarVision Almería: A Ground-Based Dataset of All-Sky Images, Solar Irradiance, and Meteorological Measurements - Yann Fabel; Niklas Blum; Bijan Nouri; Stefan Wilbert; Sergio Gonzalez Rodriguez; Luis Zarzalejo (PANGAEA, 2025)
This dataset provides ground-based image and sensor measurement data from a scientific research site in southern Spain (Tabernas, Almería). Its main contributions include all-sky images in the visible spectrum from three different fish-eye cameras capturing clouds motions, as well as diffuse, direct and global solar irradiance measurements from ISO 9060 class A spectrally flat pyrano- and pyrheliometers. The cameras and irradiance measuring devices are co-located within a radius of 20m at the same meteorological station. Image data is provided in its original resolution ranging from 4 to 8 MP depending on the camera, in 8-bit JPEG format. The dataset contains low-dynamic-range (LDR) images with fixed exposure times between 80 and 320μs. Furthermore, two cameras were temporarily configured to automatically generate high-dynamic-range (HDR) images. For one of the cameras, exposure series were captured, consisting of three sequential images with increasing exposure times. Additionally, the dataset is enriched by meteorological measurements from nearby meteorological stations (within 500m), including ambient temperature, atmospheric pressure, wind speed and direction, and relative humidity. In total, the dataset spans two years, covering August 2022 to July 2024, with measurements recorded at a 1-min resolution during daytime (solar elevation angle exceeding 5°). The primary objective of this dataset is to provide researches with high-quality sky image and irradiance data to study the effects of clouds and atmospheric turbidity on solar irradiance, as well as to investigate cloud dynamics at high spatial and temporal resolution. In addition, the dataset enables direct comparisons between different cameras and configurations, e.g. images of fixed exposure times versus HDR images, helping to identify the best camera settings for a specific application.